2015
DOI: 10.3310/hsdr03090
|View full text |Cite
|
Sign up to set email alerts
|

Insights from the clinical assurance of service reconfiguration in the NHS: the drivers of reconfiguration and the evidence that underpins it – a mixed-methods study

Abstract: BackgroundOver the life of the NHS, hospital services have been subject to continued reconfiguration. Yet it is rare for the reconfiguration of clinical services to be evaluated, leaving a deficit in the evidence to guide local reconfiguration of services.ObjectivesThe objectives of this research are to determine the current pressures for reconfiguration within the NHS in England and the solutions proposed. We also investigate the quality of evidence used in making the case for change, any key evidence gaps, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 72 publications
0
31
0
Order By: Relevance
“…Smith noted that conceptualising, measuring, and improving efficiency in health care is fraught with difficulty. A 2015 review by Imison et al of 123 proposed reconfiguration projects in the UK found no evidence of significant savings resulting from reconfiguration. It is noteworthy that most reconfiguration in Ireland occurred in rural areas, where significant investment in community and ambulance services would normally be required to alleviate the harms associated with reduced access .…”
Section: Discussionmentioning
confidence: 99%
“…Smith noted that conceptualising, measuring, and improving efficiency in health care is fraught with difficulty. A 2015 review by Imison et al of 123 proposed reconfiguration projects in the UK found no evidence of significant savings resulting from reconfiguration. It is noteworthy that most reconfiguration in Ireland occurred in rural areas, where significant investment in community and ambulance services would normally be required to alleviate the harms associated with reduced access .…”
Section: Discussionmentioning
confidence: 99%
“…20 A 2015 review of 123 proposed reconfiguration projects in the UK found no evidence of significant savings resulting from reconfiguration. 21 Finally, a 2014 UK study found that most of the variation in potentially avoidable emergency admissions is due to factors such as socioeconomic deprivation, which are beyond the control of health services. 22…”
Section: Summary Of Siren Findingsmentioning
confidence: 99%
“…In recent health services research, public responses to NHS change proposals have predominantly been approached as a monolithic obstacle to progress, and policy reports have urged decision makers to “take tough decisions” (Brooks and Farrington‐Douglas , Imison et al . ). Rather than question how healthcare organisations can overcome public attachment to hospitals, this paper asks how local hospitals have meaning for their communities, and what roles communities play in their change and closure.…”
Section: Introductionmentioning
confidence: 97%